Public School Nurses in the United States: National School Nurse Workforce Study 2.0. - Willgerodt, Mayumi A.; Tanner, Andrea; McCabe, Ellen; Jameson, Beth; Brock, Doug (Journal of School Nursing, 2024)
The National School Nurse Workforce Study 2.0 describes the demographic characteristics and distribution patterns, school nursing models and activities, and practice environment among self-reported public school nurses in the United States. A random sample of U.S. public schools was surveyed, stratified by region, school level, and urban/rural locale. A total of 2,827 schools responded, yielding a 38.1% response rate. Using these data, we estimate 78,869 full-time equivalents of school nurses, with 65,052 registered nurses (RN) and 13,817 licensed practical/vocational nurses (LPN/LVN). Findings indicate school nurse distribution differences by region, locale, and income. The predominant model of school nursing practice was the RN only, followed by the RN and LPN model. In general, school nurse respondents felt supported by school staff and parents. Less than half of survey respondents stated they were supervised by an RN. Research, policy, and school nursing practice implications are discussed.